Manic episodes are related to changes in frontal cortex: a longitudinal neuroimaging study of bipolar disorder 1. (15th September 2015) - Abé, Christoph; Ekman, Carl-Johan; Sellgren, Carl; Petrovic, Predrag; Ingvar, Martin; Landén, Mikael
Abstract : In a longitudinal structural MRI study of bipolar disorder, Abé et al. reveal a reduction in volume of frontal cortex in patients who experience manic episodes, but not in those who remain well. The results suggest that frontal grey matter loss in bipolar disorder can be attributed to the occurrence of mania. Abstract : Abstract : Higher numbers of manic episodes in bipolar patients has, in cross-sectional studies, been associated with less grey matter volume in prefrontal brain areas. Longitudinal studies are needed to determine if manic episodes set off progressive cortical changes, or if the association is better explained by premorbid brain conditions that increase risk for mania. We followed patients with bipolar disorder type 1 for 6 years. Structural brain magnetic resonance imaging scans were performed at baseline and follow-up. We compared patients who had at least one manic episode between baseline and follow-up (Mania group, n = 13) with those who had no manic episodes (No-Mania group, n = 18). We used measures of cortical volume, thickness, and area to assess grey matter changes between baseline and follow-up. We found significantly decreased frontal cortical volume (dorsolateral prefrontal and inferior frontal cortex) in the Mania group, but no volume changes in the No-Mania group. Our results indicate that volume decrease in frontal brain regions can be attributed to the incidence of manic episodes.